LECTURERS STRATEGIES ON TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) AT MANAGEMENT DEPARTMENT. - Pongmararre, Moris (Publikasi dan UKI Press UKI Toraja., 2024)
The purpose of this study is to find out the teaching strategies used by lecturers in the management department for certain purposes and how students think of the teaching strategies used by lecturers in learning English for specific purposes. For data processing in this study researchers used qualitative methods, the strategy used was qualitative descriptive. The subject of the study was an English lecturer who taught in the management department and obtained through interviews and voice recordings. The data that has been collected is analyzed in three stages, namely information reduction, information display and conclusion drawing. The results showed that the lecturers' strategies in teaching English for Special Purposes (ESP) in the management department contained 5 parts, namely: Just a Minute (JAM), Group Discussion, Discussion, Presentation, and Role playing.